Detection of Egg Production of Tegal Duck by Blood Protein Polymorphism - Ismoyowati, Ismoyowati (ANIMAL PRODUCTION, 2008)
The aim of this research was to study the effect of transfferine, albumine, and haemoglobine loci to egg production characteristic of Tegal duck.  100 lying of Tegal ducks keeping by batteray-pen were used in this study.  Individual egg production was recorded until period of 120 days. Blood protein polymorphism analysed by electrophoresis method, and blood sample taken from each ducks.. Egg production and transfferine albumine, and haemoglobine phenotipe on electrophoresis gel were observed in this study.  Genotipe and gene frequencies and genetic variant were applied in data analysis. The result showed that (1) in the transferine locus were identified 3 aleles forming 4 genotipes (TfAA,TfAB, TfBB, and TfBC), (2) in albumine were identified 3 aleles forming 5 genotipes (AlbAA, AlbAB, AlbAC, AlbBB and AlbBC) and (3) haemoglobine locus were identified 6 aleles forming 4 genotipes ((HbAA, HbAB, HbAC, HbBB, HbBC dan HbCC).  This study demostrated that B gene frequenci in transfferine, albumine and haemoglonine loci was highest than A and C gene frequency.  Tegal Duck with AA genotipe on all loci had higher egg production than BB and CC homozigote.  This research revealed that the most efective of selection method by haemoglobine protein polymorphism. (Animal Production 10(2): 122-128 (2008) Key Words: Tegal duck, egg production, selection, blood protein polymorphism